The appointment of judges in Ecuador: In search of a new legitimacy - Miguel Herrera (Íconos)
The reforms to the judiciary in Ecuador undertaken during the government of Rafael Correa have given rise to a significant number of reflections in the academic world. Most analysts have focused on evaluating their legal and constitutional basis, as well as their impact on the independence of this state power. However, less attention has been paid to the concrete mechanisms of institutional change on which these initiatives were based. Reforms such as those carried out during the Correa administration are more than attempts to capture the country's courts, insofar as they reflect dynamics to redefine the judicial institution. To explore this proposal, the article relies on the qualitative analysis of the trajectories of members of the main Ecuadorian court of justice between 1979 and 2012. It is shown that changes made to appointment procedures modified the social dynamics that had historically enabled access to the main judiciary. Specifically, with the reforms undertaken during Correa's term, greater specialization in judicial activity was privileged over career models based on professional mobility outside the courts. Thus, the social dynamics that have sustained reform initiatives are examined, showing how they are driven by different groups within social space.